COMPARATIVE DATA ANALYSIS OF REPRODUCTIVE AND MILK YIELD PERFORMANCE OF HOLSTEIN FRIESIAN AND SWEDISH RED CATTLE UNDER ORGANIC FARMING CONDITIONS IN TURKIYE - Bahri Bayram; Veysel Fatih Özdemir; Oguz Fatih Ergün (Journal of Animal and Plant Sciences, 2026)
In Türkiye, the cattle population has increased by 56% in the last quarter century. The number of cattle has risen from 10.7 million to 16.8 million. 70.4% of the annual red meat production and 93.6% of the milk production in the country originate from cattle. Almost all of this production comes from dairy breeds. As in other countries, the increasing demand for organic milk and dairy products in the country has led to the conversion of some dairy cattle to organic production. However, the search continues for the most suitable breeds for organic dairy farms operating under limited and restricted conditions, particularly regarding concentrate feed ratios. This study aims to identify the most suitable breed by comparing some reproductive and milk yield characteristics of Holstein Friesian and Swedish Red cattle raised organically in Türkiye. For this purpose, fertility and milk yield records of 1559 HF and 339 SR cows belonging to a private organic dairy farm operating in Kelkit district of Gümüşhane province in the Eastern Black Sea Region of Türkiye covering the years 2007-2012 were used. HF and SR heifers reached first calving age at 29.8 and 26.1 months, respectively, in other words, SR heifers reached first calving age 3.7 months earlier (P<0.01). Calving interval in HF and SR cows was determined as 406.1 and 380.8 days, respectively, and the difference was significant (P<0.05). HF cows had a longer service period (9.3 days) (P<0.05). The number of days milked was determined as 350.5 and 322.4 days in HF and SR cows, respectively, with a significant difference of 28.1 days in favor of HF (P<0.01). HF cows had a 305-day milk yield of 522 kg more, but this difference was not significant. While actual milk yield of HF cows was 1.074 kg higher (P<0.05). SR cows reached the peak point earlier (10.7 days) (P<0.05). In both breeds, positive and significant (P<0.01) relationships were determined between the first calving age and the number of days of milking between calving, and actual milk yield. In both breeds, a positive and significant relationship (P<0.01, P<0.05) was detected between calving interval and days in milk as well as actual milk yield. In other words, antagonistic relationships were determined between fertility and milk yield in both breeds. The findings of present study indicate that SR cows raised under organic conditions in Türkiye exhibit superior reproductive performance and maintain comparable milk yield characteristics. Overall, the findings reveal a breed-specific trade-off between reproductive robustness and lactation persistence under organic production constraints, indicating that SR cows may be better suited for organic systems that prioritize fertility, regular calving intervals, and long-term herd sustainability.
Keywords: Organic cattle farming; Reproductive performance; Milk yield; Holstein Friesian; Swedish Red; Phenot